The dynamics of Peruvians who do not study or work: who they are, how are they doing and how they have changed - Tavera, José (2017)
We analyze the dynamics of the Peruvian NEET population during the last two decades using data from the Peruvian National Household Surveys. We identify the NEET population and its characteristics, classifying it by intensity. We find that the NEET population is primarily urban, made up of women and individuals who have just finished high school. Additionally, we find that a large proportion of women in the NEET population are willing to work. Finally, we observe that the proportion of NEET among the young population is declining over time.